Analisis Framing Tempo.co Terhadap Kontroversi Proyek Strategi Nasional PIK 2 - Irwansyah, Cecep; Soekowati, Gede Moenanto; Nasirin, Anas Anwar (Universitas Muhammdiyah Yogyakarta, 2025)
This study aims to analyze the framing of media coverage by Tempo.co regarding the controversy surrounding the development of Pantai Indah Kapuk (PIK) 2, which has been associated with the status of a National Strategic Project (Proyek Strategis Nasional or PSN). The research adopts a qualitative approach using Robert N. Entman’s framing analysis model, which includes four key elements: define problems, diagnose causes, make moral judgments, and treatment recommendations. The study focuses on four news articles published by Tempo.co on January 5, 8, 13, and 18, 2025. The findings reveal that although the reports highlight significant issues such as social inequality, environmental degradation, and spatial planning conflicts, Tempo.co tends to adopt a cautious stance in criticizing the government. The narratives primarily emphasize statements from political elites and government officials, often avoiding direct confrontation. The statement by the Coordinating Minister for Economic Affairs clarifying that PIK 2 is not a PSN further illustrates the lack of transparency in public information. These findings indicate that the media has not fully exercised its social control function. Therefore, it is crucial for the press to be more courageous in voicing social justice, especially when public aspirations are suppressed through legal mechanisms.